General Principles to Justify Plant Biostimulant Claims - Ricci, Manuele; Tilbury, Lorraine; Daridon, Bruno; Sukalac, Kristen (Frontiers in Plant Science, 2019)
The forthcoming European Union (EU) Fertilizing Products Regulation proposes a claim-based definition of plant biostimulants, stipulating that "plant biostimulant" means a product stimulating plant nutrition processes independently of the product's nutrient content, with the aim of improving one or more of the following characteristics of the plant: nutrient use efficiency, tolerance to abiotic stress, crop quality traits or availability of confined nutrients in the soil and rhizosphere . The future regulation also specifies that a plant biostimulant “shall have the effects that are claimed on the label for the plants specified thereon”. This creates an onus for manufacturers to demonstrate to regulators and customers that product claims are justified. Consequently, the justification of the agronomic claim of a given plant biostimulant will be an important element to allow it to be placed on the EU market once this new European regulation is applied. In this article, members of the European Biostimulant Industry Council (EBIC) propose some general guiding principles to follow when justifying plant biostimulant claims, that are outlined in this article. These principles are expected to be incorporated into harmonized European standards that are being developed by the European Committee for Standardization (CEN) to support the implementation of the regulation.